2013
DOI: 10.3109/08880018.2013.771388
|View full text |Cite
|
Sign up to set email alerts
|

Determining and Surveying the Role of Carnitine and Folic Acid to Decrease Fatigue in β-Thalassemia Minor Subjects

Abstract: Beta-thalassemia minor (BTM) patients usually experience fatigue, bone pain complaint, and muscle weakness. Carnitine is an essential protein for transportation of long-chain fatty acids to the matrix for beta-oxidation. BTM patients have abnormally low plasma carnitine concentrations, which results in deficient ATP production. Carnitine and folic acid together may have a role in preventing bone pain complaint and fatigue in these patients. The aim of this study is to determine the effect of carnitine and foli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Folate (vitamin B9) supplementation has been successfully tested in patients with beta-thalassemia, an inherited disorder in which red blood cells and hemoglobin levels are affected, leading to fatigue and muscular weakness. In spite of some methodological drawbacks, it has been found that, in 73 thalassemic children aged approximately 10 years, folic acid supplementation (1 mg/day for 3 months) led to a reduction of reported fatigue perception [122].…”
Section: Supplementation With Individual B Vitamins and Physical Fatiguementioning
confidence: 99%
“…Folate (vitamin B9) supplementation has been successfully tested in patients with beta-thalassemia, an inherited disorder in which red blood cells and hemoglobin levels are affected, leading to fatigue and muscular weakness. In spite of some methodological drawbacks, it has been found that, in 73 thalassemic children aged approximately 10 years, folic acid supplementation (1 mg/day for 3 months) led to a reduction of reported fatigue perception [122].…”
Section: Supplementation With Individual B Vitamins and Physical Fatiguementioning
confidence: 99%
“…While et al show that the leading symptom of sickle cell anemia is chronic fatigue and complaints of pain [ 112 ]. In the context of fatigue therapy, Tabei et al demonstrated that patients with beta-thalassemia minor anemia have low levels of free and total plasma carnitine and reported the efficacy of carnitine and folic acid supplementation in reducing fatigue and muscle weakness in these patients [ 113 ]. They studied 73 children with beta-thalassemia minor, evaluating their laboratory parameters and the level of plasma-free carnitine, total carnitine, red blood cell folate, and hemoglobin.…”
Section: Clinical Presentation Of Iron Disturbancesmentioning
confidence: 99%
“…The β-thal minor patients usually experience bone pain complaint, muscle weakness, myalgia and fatigue 57 . Abnormal low plasma carnitine concentrations which lead to deficient ATP production, fatigue and bone pain complaint has been reported in these patients and carnitine and folic acid supplementation lead to a decrease in muscle weakness and bone pain complaint 58 . β-thalassemia intermedia .Genetic heterogeneity of β-TI is associated with wide clinical spectrum manifestation from mild to severe hemolytic anemia.…”
mentioning
confidence: 95%